PHILOSOPHICAL ANALYSIS OF A PERSON’S SELF-REFLECTION IN THE CONTEXT OF INTERNAL DIALOGUE (BASED ON "THE DISPUTE OF A MAN WITH HIS BA") - V. V. Liakh; M. V. Lukashenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The study is aimed at considering self-reflection through an analysis of the features of internal dialogue in ancient texts (XXII-XXI centuries BC) in order to identify signs of human’s mythological and philosophical thinking. Theoretical basis of the work is the contemplation of a person’s self-reflection in the context of his internal dialogue, through which his own human existence, his subjective and creative comprehension of the world manifest. New meanings are created and shared with others in this mental space, in particular, in crisis periods of personal and social life. Therefore, the ancient Egyptian vision of man’s nature, consciousnesses and dialogism of the Self is viewed through the prism of modern philosophical concepts and as the basis for the emergence of a philosophical worldview itself. Originality. The analysis from the viewpoint of the philosophical anthropology in the text "The Dispute of a Man with His Ba" showed the opportunity of considering it not only in the context of internal dialogue, but also as a confirmed internal dialogue, which expresses itself in external speech. Comparing the mythical thinking of a man in his cohesiveness with others and the philosophical thinking of a dialogical Self, the authors come to the conclusion that it is necessary to distinguish between internal dialogues with oneself and with the introjects of others, which can be either Double or Interlocutor. It has been revealed that internal dialogues in ancient times played an important role both in structuring social chaos and in overcoming personal crisis states (from existential to clinical states of altered consciousness). This is precisely from such self-reflection that philosophy emerges as a certain discourse and a new type of thinking. Conclusions. The analysis of the text "The Dispute of a Man with His Ba" speaks about the emergence of philosophical discourse in the XXII-XXI centuries BC, on the basis of which we can conclude concerning the earlier, in comparison with K. Jaspers’s definition, the transition of mankind from the cognitive revolution to a new phase of the development.